2011
DOI: 10.1002/elps.201000629
|View full text |Cite
|
Sign up to set email alerts
|

Some possibilities of an analysis of complex samples by a mass spectrometry with a sample pretreatment by an offline coupled preparative capillary isotachophoresis

Abstract: This work deals with an analysis of biologically important compounds in complex matrices using preparative isotachophoresis (pITP) in column coupling configuration as a sample pretreatment technique followed by a direct infusion mass spectrometry with nano-electrospray ionization (DI-nESI-MS). Busereline was chosen as a model analyte, and urine was chosen as an example of complex matrix. In pITP experiments, sodium cation (10 mmol/L concentration) was used as a leading ion and β-alanine as terminating ion (20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…The main advantages of pITP using a micropreparative valve in the single or column‐coupling arrangement of the separation unit are described elsewhere . It was demonstrated that pITP in an off‐line mode could be used successfully as a sample pretreatment technique in the analysis of different multicomponent matrices prior to applying other high‐performance analytical techniques . The preconcentration capacity and sample clean‐up effect of pITP used for sample pretreatment in an off‐line mode using a micropreparative valve were previously noted in the literature, that is prior to HPLC analysis of herbicides in soil , urine matrices , flavonoids in plant extracts , and phenolic components in wine .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The main advantages of pITP using a micropreparative valve in the single or column‐coupling arrangement of the separation unit are described elsewhere . It was demonstrated that pITP in an off‐line mode could be used successfully as a sample pretreatment technique in the analysis of different multicomponent matrices prior to applying other high‐performance analytical techniques . The preconcentration capacity and sample clean‐up effect of pITP used for sample pretreatment in an off‐line mode using a micropreparative valve were previously noted in the literature, that is prior to HPLC analysis of herbicides in soil , urine matrices , flavonoids in plant extracts , and phenolic components in wine .…”
Section: Introductionmentioning
confidence: 90%
“…Preparative isotachophoresis (pITP) has been shown to be a powerful sample pretreatment technique . The main advantages of pITP using a micropreparative valve in the single or column‐coupling arrangement of the separation unit are described elsewhere . It was demonstrated that pITP in an off‐line mode could be used successfully as a sample pretreatment technique in the analysis of different multicomponent matrices prior to applying other high‐performance analytical techniques .…”
Section: Introductionmentioning
confidence: 99%
“…Separation of buserelin from the urine matrix was reached by cationic ITP with discrete spacers and the LOD of the method was in the 10 pM range. The same technique was used for the determination of buserelin by direct infusion nano‐ESI MS and MS/MS and for the analysis of buserelin and other therapeutic peptides (anserine and carnosine) in urine by CZE‐ESI‐MS . The LODs for the latter method were all below one mg/L.…”
Section: Instrumentation and Techniquesmentioning
confidence: 99%
“…The main advantages of MS detection include (i) an improvement of detection sensitivity as well as (ii) the capability of both determining the exact mass and/or fragmentation of analytes and providing structural information including the possibility to identify and determine comigrating species in overlapping peaks (peak purity and identity) . Hence, a CE‐MS combination can offer a lot of benefits, mainly, short analysis time, sensitivity and separation efficiency, minimal sample and electrolytes consumption, and high detection selectivity and sensitivity . So far, one of the most commonly used mass analyzers in LC‐MS is the triple quadrupole (3Q), which provides one of the best sensitivity parameters.…”
Section: Introductionmentioning
confidence: 99%